Chronic Posterior Dislocation of the Glenohumeral Joint Complicated by a Fractured Proximal Humerus: A Case Report - K Takase; A Watanabe; K Yamamoto (Journal of Orthopaedic Surgery, 2006)
A 41-year-old right-handed woman was involved in a traffic accident and landed on the right arm while the right shoulder was in flexion. She experienced pain and severe impairment of right shoulder motion immediately following the accident. She was misdiagnosed with a fractured proximal humerus with no displacement and was treated conservatively by immobilisation. There was inadequate recovery in range of motion and gradual development of severe pain. Two years and 4 months after the injury, the patient presented to our hospital where a diagnosis of chronic posterior fracture dislocation of the shoulder with split articular surface of the humeral head was made. A humeral head replacement without resection of the greater tuberosity or the coracoid process was performed. Postoperative recovery was uneventful. The patient returned to work as a cook one year later. At 20-month follow-up, the patient had no pain, and her shoulder range of motion was forward flexion 160 degrees, abduction 140 degrees, external rotation 40 degrees, and internal rotation L3.